Strength reduction in square columns confined with CFRP under marine environment. (15th July 2016) - Subhani, Mahbube; Al-Ameri, Riyadh
Abstract: The performance of carbon fibre reinforced polymer (CFRP) wrapped square column under the wet/dry cycle of marine environment is studied in this paper. Two different types of epoxies (one commercial and one modified) are used to bond CFRP with concrete to investigate their suitability under the harsh environmental exposure. The experimental results are verified against the available theoretical models of square column and a reduction factor is derived to incorporate the effect of marine exposure to estimate the strength reduction for the columns in general. The accuracy of the proposed reduction factor is then verified by predicting the degraded strength of the columns which are currently available in the literature.